The Importance of Evaluative Thinking and the Excess of Scientific Effectiveness - Inspirations from Henryk Elzenberg’s Thought - Łukaszewska, Katarzyna (Ruch Filozoficzny, 2021)
The dynamics of changes in science inevitably, but also increasingly urgently begins to include ethical reflection. These issues include such problems as: the gap between the prestige of scientific and didactic activity, building scientific achievements solely through the prism of their carrying capacity, or the lack of influence of science on social and cultural life. The dominant role in shaping teaching standards is played by such phenomena as parameterization, indexing, coefficients or accreditation, while the normative space of scientific activity is no longer subject to such obvious standardization. The educational and cultural role of the people of science devalues towards entrepreneurship and effectiveness. Based on Henryk Elzenberg’s views on the excess of the importance of science to the detriment of evaluative thinking, it can be noted that contemporary academic expertise does not seem to pursue any axiological connotations, which in the long run is a highly disturbing advantage for culture.